Einfache Energieumsatzstudien an verschiedenen Oberflächen und Materialschichten der Geosphäre - Werner, Julius (ERDKUNDE, 1985)
This paper attempts to show the possibility of simulating temporal developments of temperature in soil structures near the surface and in layers of asphalt during the course of geoscientific field studies by the application of simple instrumental and mathe matical methods. All the necessary input parameters can be measured comparatively easily, in situ. In so far as the specific heat and density of the layers of material studied are known, this will produce satisfactory conformity between temperatures thus measured and those median temperatures of the layers calculated on the basis of hourly energy balances. The application of this method seems promising for objects of climatological significance in open country and in cities, e.g. to forecast micro-climatological effects of anthropogenic activities